Pinpointing clusters of apparently sporadic cases of Legionnaires' disease. Issue 6833 (18th April 1992) - Bhopal, R. S.; Diggle, P.; Rowlingson, B.
Abstract : OBJECTIVES–To test the hypothesis that many non-outbreak cases of legionnaires' disease are not sporadic and to attempt to pinpoint cases clustering in space and time. DESIGN–Descriptive study of a case series, 1978-86. SETTING–15 health boards in Scotland. PATIENTS–203 probable cases of non-outbreak, non-travel, community acquired legionnaires' disease in patients resident in Scotland. MAIN MEASURES–Date of onset of disease and postcode and health board of residence of cases. RESULTS–Space-time clustering was present and numerous groups of cases were identified, all but two being newly recognised. Nine cases occurred during three months within two postcodes in Edinburgh, and an outbreak was probably missed. In several places cases occurred in one area over a prolonged period–for example, nine cases in postcode districts G11.5 and G12.8 in Glasgow during five years (estimated mean annual incidence of community acquired, non-outbreak, non-travel legionnaires' disease of 146 per million residents v 4.8 per million for Scotland). Statistical analysis showed that the space time clustering of cases in the Glasgow and Edinburgh areas was unusual (p = 0.036, p = 0.068 respectively). CONCLUSION–Future surveillance requires greater awareness that clusters can be overlooked; case searching whenever a case is identified; collection of complete information particularly of date of onset of the disease and address or postcode; ongoing analysis for space-time clustering; and an accurate yet workable definition of sporadic cases. Other researchers should re-examine their data on apparently sporadic infection.